أهمية إستراتيجية الموارد البشرية في رفع أداء المؤسسة - الوالي نور الهدى, بلهندة خيرة (My University, 2022)
This study includes the importance of the human resources strategy in raising the performance of the institution, which considers the human resource the pillar and the first advantage of excellence. This importance was addressed through a systematic sequential arrangement, where human resource management was identified, and then the strategies used, passing through the basics of performance evaluation, to arrive at how to formulate an appropriate strategy in an organization to raise the performance of workers. As a projection of this importance to the Sonatrach Foundation, the subject of the study, we came out with some results that confirm the activation of two important aspects, namely the need to pay attention to the human resource in the institution, and the possibility of raising performance through strategies followed and studied
بطيوى GL2/Zدراسة حالة مؤسسة سونطراك مركب
Keywords: This study includes the importance of the human resources strategy in raising the performance of the institution, which considers the human resource the pillar and the first advantage of excellence. This importance was addressed through a systematic sequential arrangement, where human resource management was identified, and then the strategies used, passing through the basics of performance evaluation, to arrive at how to formulate an appropriate strategy in an organization to raise the performance of workers. As a projection of this importance to the Sonatrach Foundation, the subject of the study, we came out with some results that confirm the activation of two important aspects, namely the need to pay attention to the human resource in the institution, and the possibility of raising performance through strategies followed and studied